The Application of the Principles of Ephesians 6:1–4 in the Upbringing of Children in Toraja Christian Families in Kupang - Marsi Bombongan Rantesalu; Jeni Isak Lele; Yitram Man Pay (Didache: Journal of Christian Education, 2026)
This study aims to analyse the implementation of the values of Ephesians 6:1-4 in child education within Toraja Christian families in Kupang amidst the challenges of globalisation and socio-cultural change. The research employed a quantitative survey method involving 50 respondents, with data analysed using descriptive statistics and a One-Sample t-Test supported by SPSS. The findings reveal that the implementation of the values of Ephesians 6:1-4—namely respect for parents, parental responsibility, love-based education, and moral and spiritual formation—is at a very high level and statistically significant. These results indicate a harmonious integration between biblical values and Torajan cultural principles in child-rearing practices. In conclusion, Torajan Christian families in Kupang consistently apply the teachings of Ephesians 6:1–4 as the primary foundation for child education. The study highlights the crucial role of the family as the central locus of faith formation and underscores the need for churches to strengthen family-based ministry programmes that promote contextual, biblically grounded parenting.